Greenwashing dalam Pengungkapan ESG: Tinjauan Literatur Sistematis Melalui Analisis Teoretis dan Bibliometrik - Mugisana, Radi; Eneng Nurdiana Septifani; Laras Angelia Nirwana Sari (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study aims to examine greenwashing practices in Environmental, Social, and Governance (ESG) disclosure through a Systematic Literature Review (SLR) approach combined with theoretical and bibliometric analysis, utilizing Scopus-indexed journal articles from 2019 to 2025, supported by the Watase Uake Tools platform to ensure the selection and visualization of structured and relevant article keywords. The results of the study show that greenwashing practices tend to emerge when companies face pressure for legitimacy and high stakeholder expectations, while internal capacity and governance are not yet able to support substantive sustainability practices. Manipulation of report narratives, low report readability, and inconsistent ESG reporting standards also contribute to the spread of misinformation. The findings indicate that strengthening regulations, utilizing misinformation detection technologies such as artificial intelligence (AI), and strengthening governance are strategies to mitigate greenwashing. Bibliometric mapping shows that research related to greenwashing in ESG disclosure generally focuses on issues of regulation, transparency, governance, and reporting quality, while SLR methodology and bibliometric analysis are still limited. This study offers novelty by combining SLR analysis with bibliometrics and integrating legitimacy theory and stakeholder theory to provide a more comprehensive understanding of the root causes and future directions of research.